Study on the Precise Modeling Method of Helical Gear with Deviation and Modification - Yuan Yongchao; Liu Zhongming; Mao Jizhe; Cao Yanjun; Zhang Kun (Jixie chuandong)
According to the forming process principle,the influence of the tooth profile modification,helix modification and tooth profile deviation,helix deviation and eccentricity tolerance of radial run-out of the involute helical gear on tooth profile shape is analyzed. The curve equations of the involute transverse tooth profile are derived step by step. By using the software,the curve equation of deviation is fitted,and the theoretical curve is replaced by the deviation curve. Then,the actual tooth profile model and solid model including modification and deviation of gear are generated.